2023
DOI: 10.1093/biolre/ioad007
|View full text |Cite
|
Sign up to set email alerts
|

Sialyl Lewis X mediates interleukin-1 beta-induced trophoblast adhesion to endometrial cells during human embryo implantation

Abstract: Cell surface carbohydrate antigens sialyl Lewis X (sLeX) and Lewis Y (LeY) are paramount glycoconjugates and are abundantly expressed in the receptive endometrium. Furthermore, among the important biological functions of both antigens is their role in leukocytes adhesion and extravasation. Interleukin-1 beta (IL-1β) is involved in the process of human embryo implantation and placenta development. Here we used an in vitro model to investigate whether sLeX and LeY are playing a role in the embryo implantation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…A study has found that sLeX exhibits heightened expression in both mice and humans during endometrial implantation, coinciding with the upregulation of L-selectin expression in trophoblasts [32]. The biosynthesis of sLeX is regulated by glycosylated enzymes such as fucosyltransferase 3 (FUT3), fucosyltransferase 7 (FUT7), sialyltransferase β-galactoside-α2,3-sialyltransferase III (ST3GAL3), and sLeX is also associated with MUC1 expression, promoting endometrial receptivity and mediating the adhesion of blastocyst and receptivity endometrium [52][53][54][55] (Figure 2).…”
Section: Endometrial Receptivitymentioning
confidence: 99%
“…A study has found that sLeX exhibits heightened expression in both mice and humans during endometrial implantation, coinciding with the upregulation of L-selectin expression in trophoblasts [32]. The biosynthesis of sLeX is regulated by glycosylated enzymes such as fucosyltransferase 3 (FUT3), fucosyltransferase 7 (FUT7), sialyltransferase β-galactoside-α2,3-sialyltransferase III (ST3GAL3), and sLeX is also associated with MUC1 expression, promoting endometrial receptivity and mediating the adhesion of blastocyst and receptivity endometrium [52][53][54][55] (Figure 2).…”
Section: Endometrial Receptivitymentioning
confidence: 99%